2022
DOI: 10.3390/nu14102126
|View full text |Cite
|
Sign up to set email alerts
|

Food Insecurity Reduces the Chance of Following a Nutrient-Dense Dietary Pattern by Brazilian Adults: Insights from a Nationwide Cross-Sectional Survey

Abstract: Dietary patterns derived by data-driven techniques are still scarce in the food security context and may be a useful tool to inform policymakers to promote adequate and healthy diets for vulnerable populations. We investigated the association between food security status and dietary patterns among 28,127 Brazilian adults using data from the 2017–2018 Household Budget Survey. Food security status was measured by the Brazilian Food Insecurity Scale. Food items reported in two 24 h dietary recalls were combined i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…The adoption of inappropriate eating habits has shown to have an important influence on reducing the consumption of a typically Brazilian preparation, rice and beans 31,35,36 . Beans are an important source of nutrients and the result of their combination with rice is a meal with adequate nutritional value 35 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The adoption of inappropriate eating habits has shown to have an important influence on reducing the consumption of a typically Brazilian preparation, rice and beans 31,35,36 . Beans are an important source of nutrients and the result of their combination with rice is a meal with adequate nutritional value 35 .…”
Section: Discussionmentioning
confidence: 99%
“…31 The adoption of inappropriate eating habits has shown to have an important influence on reducing the consumption of a typically Brazilian preparation, rice and beans. 31,35,36 Beans are an important source of nutrients and the result of their combination with rice is a meal with adequate nutritional value. 35 Over the years, a reduction in the purchase of traditional Brazilian foods such as beans has been observed in the social classes with higher purchasing power, and, on the other hand, an increase in the consumption of ultra-processed foods has been observed.…”
Section: Characteristicsmentioning
confidence: 99%
“…Thus, black students were more likely to have dietary inadequacies concerning adequate and regular intake of fiber, vitamins, minerals, and bioactive compounds, which may significantly impact their overall morbidity (Moriguchi Watanabe et al 2022 ; Leme et al 2021 ). When assessed more comprehensively, these disparities highlighted that, even if evaluated in a select group of the Brazilian population (in this case, university students), black individuals were the most vulnerable group in situations of food and nutritional insecurity (Salles-Costa et al 2022 ; Castro et al 2022 ), probably as a reflection of the structural racism found in Brazil, which hinders the access of these individuals to better conditions of employment, income, health, and housing (Oliveira et al 2020 ). It should be noted that the percentage of black students in this study reflects a change in the educational landscape in Brazil, achieved through affirmative policies and actions aimed at a higher inclusion of black, brown, indigenous, and low-income students in Brazilian public universities (Senkevics and Mello 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…White bread and toast are two foods commonly consumed at breakfast and intermediary meals, such as snacks, in Brazil. In the previous study with the same sample from the 2017–2018 BNDS, Castro et al (2022) identified that the dietary pattern “Brazilian breakfast style” was characterized by white breads and toasts, butter and margarine, table sugar, coffee, and natural juice [ 39 ]. It is possible that the high frequency of consumption of white bread and toast (61% of the population reported the consumption of this food group) and their high sodium content (i.e., ranging from 430 mg/100 g of homemade bread to 712 mg/100 g of toast), may explain this food group on the top of the dietary sources of sodium intake among Brazilians.…”
Section: Discussionmentioning
confidence: 99%